Тяговый асинхронный электропривод с регулированием разрядного тока аккумуляторной батареи - Шавёлкин, Александр Алексеевич; Мирошник, Денис Николаевич (НТУ "ХПИ", 2010)
In paper are considered principles of realization the vehicle asynchronous electric drive with the electric power control of charge battery. Such approach allows to improve power indicators of a vehicle by effective utilization of energy storage battery. Controllers of electric power for two base principles of frequency control: vector and scalar, are synthesized. It is shown possibility of electric power control of the vehicle drive with change of the moment of inertia.
The vehicle asynchronous electric drive with control of the charge battery current
Keywords: двигатель асинхронный; двигатель вентильно-реактивный; регулятор мощности; двигатель постоянного тока; векторное управление скоростью; скалярное управление скоростью